Analysis of South Korea's Macroeconomic Development with the Vector Error Correction Model - Ahman, Eeng; Machmud, Amir; Agus Triansyah, Fadli (Faculty of Economics, Universitas Negeri Indonesia,Indonesia, 2023)
This study examines the relationship between Gross Domestic Product (GDP), Import (IMP), Inflation (INF), and Unemployment (UNP) in South Korea using the panel vector error correction model (VECM), cointegration, and Granger. VECM is used to analyze the relationship or causality between variables involved in this research in the short and long run. From the estimation results, especially on the variables of interest, there is a positive and statistically significant relationship between Gross Domestic Product, Import, Inflation, and Unemployment, which refers more to short-term causality. Impulse Response Function analysis is used to determine the impact between variables where the results that had a positive effect during the Covid-19 pandemic were import shocks to GDP and unemployment shocks to GDP, while those that had a negative impact were inflation rate shocks to GDP in South Korea during the Covid-19 pandemic.